(untitled) (Andamios, Revista de Investigación Social, 2006)
In Filosofía de la praxis, Adolfo Sánchez Vázquez interprets praxis (an obverse whose reverse is theory) as the main category of Marxism; he applies his abstractions to concrete history and he proposes along with Feuerbach that philosophy must not only interpret, but transform the world; he compares revolutionary and creative praxes with habitual practical activity; he finds its roots in work, and defines praxis as a teleological and utopian activity, that is to say, an ethical activity: based on the wish of wellbeing with and for others within fair institutions.